Simultaneous structures in sign languages: Acquisition and emergence - Loos, Cornelia; German, Austin; Meier, Richard P. (Frontiers in Psychology, 2022)
The visual-gestural modality affords its users simultaneous movement of several independent articulators and thus lends itself to simultaneous encoding of information. Much research has focused on the fact that sign languages may coordinate two manual articulators in addition to a range of non-manuals to present different types of linguistic information simultaneously, from phonological contrasts to inflection, spatial relations, or information structure (Aronoff, Meir, & Sandler, 2005) Sandler & Lillo-Martin, 2006; Vermeerbergen et al., 2007). Children and adults acquiring a signed language arguably thus need to comprehend and produce simultaneous structures to a greater extent than individuals acquiring a spoken language. In this paper, we discuss the simultaneous encoding that is found in emerging and established sign languages; we also discuss places where sign languages are unexpectedly sequential. We explore potential constraints on simultaneity in cognition and motor coordination that might impact the learnability of simultaneous structures.